A randomised controlled trial of paracetamol and ibuprofen with or without codeine or oxycodone as initial analgesia for adults with moderate pain from limb injury - Graudins, A.; Meek, R.; Parkinson, J.; Egerton-Warburton, Diana; Meyer, A. (2016)
© 2016 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine.Objective: Compare pain relief from non-opioid, codeine and oxycodone analgesic regimens in adults with moderate pain from limb injury. Method: Double-blind, randomised, controlled, non-inferiority trial. Three regimens of six tablets, each included 2 × 500 mg paracetamol and 2 × 200 mg ibuprofen with 2 × 100 mg thiamine (non-opioid), 2 × 30 mg codeine (codeine) or 2 × 5 mg oxycodone tablets (oxycodone). Primary outcome: difference in mean visual analogue scale (VAS) change between groups at 30 min, with a limit of inferiority of 13. Secondary outcomes included mean change in VAS rating from baseline to 30 min for each group, patient satisfaction, need for additional analgesia and adverse events. Pain ratings taken at 60 and 90 min for patients still in ED are described. Results: Of 182 patients randomised, non-opioid, codeine and oxycodone numbers were 61, 62 and 59. Differences (95% CI) between groups at 30 min were as follows: non-opioid versus codeine -2.6 (-8.8 to 3.6); non-opioid versus oxycodone -2.7 (-9.3 to 3.9); codeine versus oxycodone 0.1 (-6.6 to 6.4). Mean VAS reductions for non-opioid, codeine and oxycodone were -13.5, -16.1 and -16.2 mm, respectively. Satisfaction with analgesia was reported by 77.6% (64.7-87.5), 81.0% (67.2-89.0) and 73.6% (59.7-84.7) and adverse events by 3.3% (0.4-11.3), 1.6% (0.4-8.7) and 16.9% (8.4-29.0), respectively. Mean VAS reductions at 60 and 90 min were as follows: -23.2 and -18.7 mm for non-opioid; -30.7 and -33.3 mm for codeine; and -26.1 and -31.7 mm for oxycodone. Conclusion: At 30 min, analgesic effects of non-opioid, codeine and oxycodone groups were non-inferior.